Strength training in elderly: An useful tool against sarcopenia - Cannataro, Roberto; Cione, Erika; Bonilla, Diego A.; Cerullo, Giuseppe; Angelini, Fabrizio; D'Antona, Giuseppe (Frontiers in Sports and Active Living, 2022)
The loss of muscle mass and strength in elderly population (especially after the age of 65–70) represents a public health problem. Due to the high prevalence of frailty in older adults, cardiovascular or low-intensity exercise is implemented as first choice option. Although beneficial these training schemes are not as effective as strength-based resistance training for increasing muscle strength and hypertrophy. In fact, when performed progressively and under professional supervision, strength-based training has been proposed as an important and valid methodology to reduce sarcopenia-related problems. In this mini-review, we not only summarize the benefits of weight resistance training but also highlight practical recommendations and other non-conventional methods (e.g., suspension training) as part of an integral anti-sarcopenia strategy. Future directions including cluster set configurations and high-speed resistance training are also outlined.